Context-information support for B2B collaboration. (22nd September 2009) - Tan, P.S.; Goh, A.E.S.; Lee, S.S.G.
Context information is pervasive and is being tapped by many spheres of human endeavour to enhance decision making. Examples include location-based advertisements and user personalisation. Context-aware computing to facilitate Business-to-Business (B2B) collaboration is largely unexplored. Short-term and dynamic B2B collaboration can benefit from context awareness, as the context of collaboration is often changing and such collaborations must be formed in a short time and with ease (i.e., with as little human intervention as possible). This paper focuses on a specific aspect of such collaborations, namely, partner selection, to support pervasive B2B connectivity in supply chains. It is a key ingredient for dynamic B2B collaboration. Such collaborations are expected to take place on the internet, leveraging prevalent web and context-aware technologies. The aim of this paper is to review existing literature to gather an understanding of context and how the various elements of context are modelled, and investigate how such context models can be adapted to support partner selection in B2B collaboration. The review confirms that context information has indeed not been used in supporting B2B collaboration, though some context aspects from existing context-aware applications can be adapted. As such, a more holistic approach towards the formulation of the B2B Context Model is taken, with a review of supplier selection criteria as an additional foundation for the model.